Характеристика фитопланктона реки Тверцы (Иваньковское водохранилище, Россия) - Комиссаров, А.Б.; Корнева, Л.Г. (Альгология, 2015)
Представлены результаты исследований (2009—2011 гг.) альгофлоры планктона р. Тверцы — крупнейшего притока Иваньковского водохранилища. Дана гидрохимическая характеристика реки. Проанализированы видовой состав, таксономическая структура флоры и эколого-географические характеристики планктонных водорослей. Выявлен 381 таксон водорослей рангом ниже рода. Установлено, что основу флористического разнообразия составляли Chlorophyta, Bacillariophyta, Euglenophyta и Cyanoprokaryota. Дана оценка сходства различных участков реки по видовому составу водорослей и связи богатства различных групп водорослей с абиотическими пара-метрами. Выявлена дискретная континуальность в изменении флоры планктона от истока к устью реки, обусловленная гидрохимическими факторами. The results of the studies on the algal flora of the Tvertsa River, the largest tributary to the Ivan’kovo Reservoir, conducted in 2009—2011 are presented. The chemical characterization of the river is given. Species composition and taxonomic structure of the flora are specified along with the ecological-geographical parameters of the planktic algae. Totally 381 taxa of the algae of the rank below genus are found in the river. It has been revealed that the basis of floristic diversity is composed of Chlorophyta, Bacillariophyta, Euglenophyta and Cyanoprokaryota. The similarity of various parts of the river is assessed based on the species composition of algae and relation of species richness of various groups of algae with abiotic factors. The continuity of the changes in the plankton flora along the distance from the river head to its mouth determined by the water chemical factors is revealed.